2020
DOI: 10.1055/a-1252-2942
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Clinical High Risk for Psychosis that Predict Antipsychotic Effectiveness in Long-Term Remission

Abstract: Introduction In a previous report, we used canonical correlation analysis to classify individuals with clinical high risk (CHR) of psychosis into the 3 subtypes: subtype-1, characterized by extensive negative symptoms and cognitive deficits, appeared to have the highest risk for conversion to psychosis; subtype-2, characterized by thought and behavioral disorganization, with moderate cognitive impairment; subtype-3, characterized by the mildest symptoms and cognitive deficits. The present study attempted to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Each participant signed an informed consent form, and those under the age of 18 had their guardians sign the forms (Figure 1). [14][15][16]…”
Section: Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Each participant signed an informed consent form, and those under the age of 18 had their guardians sign the forms (Figure 1). [14][15][16]…”
Section: Trial Designmentioning
confidence: 99%
“…Previous research has indicated that there may be distinct underlying pathophysiological mechanisms among different subtypes characterized by prodromal symptoms and cognitive impairment of different severities of CHR individuals for psychosis. 16 By stratifying our sample, we aimed to explore potential differences in inflammatory markers and angioneurins that may be associated with each symptom profile. Emerging evidence in the field of immunology and psychiatry indicates that inflammation plays a crucial role in the development and progression of psychotic disorders.…”
mentioning
confidence: 99%
“…Several publications have used novel analytic methods to identify neurocognitive subtypes as a means of parsing the heterogeneity among CHR [87][88][89][90]. Velthorst et al [87], using hierarchical clustering on NAPLS1 data, found that the subgroup with significant neurocognitive impairment had the greatest risk of psychotic conversion (58%) compared to mildly impaired (24%) or normal/high performance (10.3%) subgroups.…”
Section: Biomarkers Linked To Psychotic Conversionmentioning
confidence: 99%
“…In addition to having positive symptoms, PRS individuals often exhibit a certain degree of negative symptoms (such as social isolation and lack of will), disintegrating symptoms (such as strange behavior and difficulty concentrating), and general symptoms (such as sleep disorders and emotional abnormalities), which usually appear before or accompanied by positive symptoms ( McGlashan et al., 2006 ). These non-positive symptoms can reflect the severity of psychological abnormalities in PRS individuals ( Gupta, Cowan, Strauss, Walker & Mittal, 2021 ), and also have a certain impact on the clinical outcomes of PRS individuals ( Nelson et al., 2013 ; Zhang et al., 2021 ). The majority of PRS individuals have non-positive symptoms mainly characterized by anxiety and depression emotional symptoms, and the comorbidity of anxiety and depressive disorders with PRS is very common ( Fusar-Poli, Nelson, Valmaggia, Yung & McGuire, 2014 ).…”
Section: Introductionmentioning
confidence: 99%